De la Quadrak Bermeon 1784an idatzitako eskuizkribuak: I. "Doctrina christinaubarena" - Bilbao, Gidor (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1997)
Nicolás Manuel de la Quadra Villalón was born in Bilbao in 1713. In the Carmelite convent of Markina there are two manuscripts signed by this friar in the Franciscan convent of Bermeo in 1784: Doctrina christinaubarena and Exercicio santo de ayudar a bien morir. Doctrina christinaubarena, which is long compared to similar manuscripts of the same period, is not a translation of a foreign catechism, but a Basque version based on various sources. In Exercicio santo de ayudar a bien morir, which includes some short clarification notes in Spanish, different types of prayers are offered in Basque for those who help those who are about to die. Although De la Quadra writes for all Basque speakers, he does so specially for those of the area of Bermeo, Mundaka and Almike. This manuscript thus constitutes the only evidence of the Basque spoken at that time in and around Bermeo. This first part includes the introduction and the edition of Doctrina christinaubarena. The second part will be devoted to the edition of Exercicio santo de ayudar bien morir.